Analisis Potensi Kekeringan Geomorfologi Menggunakan Sistem Informasi Geografis Di Kabupaten Purworejo - Arsaninghyang, Poppy; , Drs. Yuli Priyana, M.Si (2017)
Geomorphology drought is a natural phenomenon that occurs on the surface of the earth. Drought is always threatened when the dry season arrives for the indispensable mapping of potential drought geomorphology in Purworejo which will provide information on areas of potential drought geomorphology in Purworejo research objectives: (1) determine the distribution of the level of potential drought geomorphology in Purworejo, and (2) analyze the dominant factors that potentially drought geomorphology in Purworejo. The method used in this research is secondary data analysis method. Secondary data analysis method consists of secondary data processing method, data processing method and data analysis methods include methods of GIS analysis. GIS analysis in the form of a tiered quantitative methods to produce maps of potential drought geomorphology. The parameters used in the study is the slope, drainage, land use, and soil texture. GIS analysis form kuanlitatif tiered method to determine the dominant factor affecting the potential drought geomorphology in Purworejo. Results of the study were divided into three classes include low grade, medium grade and high grade. Low-grade classification of landforms Marine is located in the southern part of Purworejo with a percentage of 5%, the classes were in the middle of landforms Fluvial Purworejo with a percentage of 39%, while high-grade classification of landforms Denudasional are in the northern part of Purworejo with a percentage of 55%. The dominant factor affecting the occurrence of drought geomorphology in Purworejo is a slope and soil texture. Slope that affect drought geomorphology is rather steep slope, steep slope, and the slope is steep while the drought affecting geomorphological soil texture is clay.